Laboratory manifestations of fetal inflammatory response syndrome in extremely premature newborns - V.V. Bila (Репродуктивная эндокринология)
Background. Fetal inflammatory response syndrome (FIRS) is a pathological response to changes in the chorion and is manifested by inadequate cytokine production and endothelial dysfunction. Objective of the study: to investigate laboratory changes in extremely premature newborns depending on the presence of FIRS criteria. Materials and methods. The prevalence of umbilical cord blood leukocytosis and leukopenia, anemia and thrombocytopenia, as well as increased levels of C-reactive protein and procalcitonin in 403 premature newborns was analyzed depending on the presence of FIRS laboratory criteria. Newborns were divided depending on the gestational age (I and II groups – 24–27 weeks, III and IV groups – 28–34 weeks), and the presence of prenatal rupture of the fetal membranes (I and III groups) or the onset of labor with intact membranes (II and IV groups). Results. FIRS increases the frequency of leukopenia, anemia, and thrombocytopenia in extremely premature newborns, and the frequency of leukocytosis and the appearance of young forms of leukocytes in premature infants from early preterm labour. Elevated levels of C-reactive protein and procalcitonin were more common in cases of premature rupture of membranes than in cases of labor with intact amniotic sac. This frequency did not depend on the presence of FIRS in extremely premature newborns; such dependence was outlined for premature infants from early preterm labour. Conclusions. Leukopenia is more often found in premature babies from very early premature births than from early premature births. More than 20 × 109/ml leukocytosis and an increased proportion of young forms of neutrophils of more than 10% were found in the case of premature rupture of the fetal membranes, more often than during childbirth with intact membranes. In extremely premature newborns FIRS was accompanied by an increased frequency of leukopenia, thrombocytopenia, and anemia. FIRS do not increase levels of C-reactive protein and procalcitonin in extremely premature newborns.